Treatment of bilateral staghorn nephrolithiasis using percutaneous nephrolithotripsy in a patient chronically infected with Proteus mirabilis: a case report with literature review - Gracjan Rudziński; Kinga Brzuszkiewicz; Natalia Kusak; Kinga Pożarowska; Krystian Cholewa; Ewa Niezabitowska (Kazimierz Wielki University, 2022)
Although urolithiasis is a common disease in the European population, bilateral staghorn stones are a relatively rare variant of nephrolithiasis. It is often associated with a chronic urinary tract infection or a metabolic disorder. The aim of this paper is to show an example of the treatment of bilateral staghorn  stones in a patient chronically infected with a resistant strain of Proteus mirabilis. Percutaneous nephrolithotripsy (PCNL) is currently the gold standard of treatment.  And this is the way the patient was managed. In the following section, the authors sought to describe new reports on this treatment method and how it could be improved.  Conservative treatment does not appear to be a safe alternative. And of the other surgical treatments, PCNL has the greatest benefits. Nearly 68% of patients with bilateral staghorn  stones have some underlying metabolic disorder in a small sample of patients. It seems reasonable, therefore, to introduce genetic and metabolic diagnosis in younger patients with the aim of prevention through diet or pharmacotherapy.